Bioaccumulation of aluminum by Lemna gibba L. from secondary treated municipal wastewater effluents - Öbek, Erdal; Şaşmaz, Ahmet (My University, 2011)
In this study, Lemna gibba as a sample aquatic plant was used to remove Al from a municipal secondary waste water effluence. Lemna gibba was acclimatized to the effluent in situ. The concentration of Al in the plant samples was examined for 7 days. Lemna gibba accumulated 500 ?g Al g?¹ on the first day and reached saturation level with an increase of 100 ?g g?¹ on the second day. The results indicated that Lemna gibba can be used as an effective aquatic plant at low costs for the treatment of municipal secondary waste water effluent. It was also noted that the plant should be harvested every 2 days for obtaining maximum efficiency.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Aluminum; Lemna gibba; Accumulation; Removing; Secondary waste water effluent